Հայրենիք – Սփյուռք հարաբերությունների էվոլյուցիան ՀՀ երեք նախագահների օրոք - Պողոսյան, Մայրանուշ
Цель статьи - представить динамику развития отношений между Родиной и Диаспорой в период правления трех президентов Армении - Левона Тер-Петросяна, Роберта Кочаряна и Сержа Саргсяна. Поскольку позиции трех президентов Армении по поводу отношений Родина-Диаспоранесколько отличались друг от друга, задачабылапоставленав том, чтобы исследовать, анализировать, координировать развитие этих отношений на основе научных исследований, статей, прессы, интернета и других источников, которые, по нашему мнению, имют актуальное значение.Представлена сдержанность отношений Армении –Диаспоры при президенте Л.Тер-Петросяне, развитие при президенте Р. Кочаряне и их укрепление при президенте С. Саргсяне. Изученная динамика позволяетсделать вывод о том, что во время правления трех президентов Республики Армения отношения между Родиной и Диаспорой развивались в направлении прогресса, развития и подъема. The aim of the article is to represent the dynamics of the development of Homeland - Diaspora relations during the rule of three different presidents of Armenia - Levon Ter - Petrosyan, Robert Kocharyan and Serzh Sargsyan. Since the positions of three presidents of Armenia regarding the relations of Homeland-Diaspora were somewhat different from each other, the main tasks held in the article are as follows: to explore, analyze, coordinate and cover the development of these relations based on some scientific studies, articles, press, the Internet and other sources. The restraint of relations between Armenia and Diaspora under President L.Ter-Petrosyan, the development under President R. Kocharyan and their strengthening under President S. Sargsyan are presented in this article. Summing up, one may conclude, that during the rule of the three presidents of the RA, the Homeland-Diaspora relations have been pursued in the direction of progress, development and rise.
Keywords: Հայոց պատմություն